Community Results-Based Financing in Health Practice : Reflections on Implementation from Experiences in Six Countries - Falisse, Jean-Benoit; Vergeer, Petra; Gebre Medhin, Joy; Juquois, Maud; Akpamoli, Alphonse; Robyn, Jake; Shu, Walters; Zabiti, Michel; Hassan, Rifat; Jallow, Bakary; Loum, Musa; Ndizeye, Cedric; et al. (World Bank, Washington, DC, 2017)
The term ‘community Results-Based Financing’ (cRBF) has been used to qualify a range of schemes whereby community actors such as community organizations, community health workers (CHW), and health facility committees (HFC) are contracted to facilitate access to ‒and sometimes directly provide‒ preventative, promotional, and curative health-care services.It is too early to assess the effects of such experiences in the countries this brief focusses on (i.e. Benin, Cameroon, the Gambia, the Republic of Congo, and DR Congo), but comparing and discussing those schemes reveal aspects that are key in implementation, among others:Pre-cRBF community engagement in health-care varies a lot; successful implementations of cRBF have built on those features and peculiarities.Timely payment is crucial in a context where community actors often live in poverty; forms of pre-payment may improve retention and motivation.Central to quality is the training and monitoring of community actors, which is easily undermined by low commitment of district officers and chief nurses. Certification and focus on the lower levels of ‘cascading’ training may improve quality, as well as testing the knowledge of community actors.Information and Communication Technology is not a panacea for improving data collection and analysis: it requires a strong system in place, simple tools, and trained, supervised, and monitored actors‒three conditions rarely met in the field. cRBF is not always well integrated into health information systems.The choice of indicators and bonuses is often a top-down decision, more community engagement may be desirable but has to be accepted by the Ministry of Health. cRBF schemes are part of wider community health policy reforms and represent an entry door to re-vitalize the often neglected sector of community health.